Business ethics and economic growth: An empirical analysis for Turkish economy - Ekrem Erdem; Can Tansel Tugcu (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2015)
Purpose - The roots of the science of modern economics are originated from the ideas of Adam Smith who is not a pure economist but a moralist-philosopher. Basic concepts in the Wealth of Nations which is perceived as the hand book of economics depend on the arguments that Adam Smith suggests in his Theory of Moral Sentiments. In this theory, business ethics as a part of the Law of Sympathy appears as one of the factors that provide the invisible hand to operate properly. In light of this property, it is possible to assume business ethics as one of the components of the market mechanism. In this context, this study aims to analyse the link between business ethics and economic growth in the Turkish economy. Design/methodology/approach - The study employs bounced cheques and protested bonds for representing the degradation of business ethics and tries to show how this degradation affects economic growth in the Turkish economy for the period 1988-2013. Findings - Either illustrative or empirical results show that business ethics is an important determinant of economic growth in the Turkish economy and damaging it negatively effects the growth rate of the economy. Research limitations/implications - One of the most restrictive things conducting the present empirical analysis is the lack of various and longer data sets. Using different indicators in terms of business ethics with longer time span will definitely increase the reliability of the study. However, in the current form, results imply a policy that is capable of limiting the failures of business ethics may boost the Turkish economy up. Originality/value - The results tend to support the close link between business ethics and economic growth.
Keywords: O47; 330; Business ethics; Economic growth; Turkish economy